Innovation Networking, Knowledge Transdisciplinary Spaces - Pop, Ioan Gh.; Fotea, Ioan S.; Fotea, Silvia L. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
In this paper a novel approach on knowledge integration in presented in the context of the knowledge-based society/economy (KBS/E). What this paper brings new is the transdisciplinary integrative approach of the knowledge through the "conceptual knowledge space" as a potentiality, and the "practical transdisciplinary knowledge space", as actuality, with the transition between them through the included middle. Are introduced some of the most important practical educational environmental transdisciplinary conceptual and applied spaces, as innovative groundbreaking clusters that foster the origination, transfer and implementation of knowledge in the process of achieving sustainable development of the continuously integrative society. The University is considered the most appropriate space for this transdisciplinary approach of knowledge achievement, being a natural habitat of the synergistic integration of education, research and industry, and with its adaptability and adequateness in the knowledge economy space. University should become an open space in a reconfiguration in a integration of a highrequired degree with breadth profile competence in the integrated fields of different disciplines, with the need to have a depth profile of the knowledge in research on particular cognitive field. A new redefined mission of university by collaborating with industry should be linked to a redefinition of the role of the research in universities in the knowledge based society/economy.